Antioxidant enzyme and malondialdehyde levels in patients with social phobia - Atmaca, Murad; Kuloglu, Murat; Tezca, Ertan; Ustundag, Bilal (Elsevier Ireland Ltd, 2008)
A growing body of reports have indicated that free radicals are involved in the etiopathogenesis of some neuropsychiatric disorders. In the present study, we aimed to evaluate whether antioxidant enzymes (superoxide dismutase; SOD, glutathione peroxidase; GSH-Px, and catalase; CAT) activity levels and malondialdehyde (MDA), a product of lipid peroxidation, were associated with social phobia (SP). Eighteen patients diagnosed with SP and 18 healthy controls were enrolled. A clinical evaluation and measurements of MDA, SOD, GSH-Px and CAT were performed. Additionally, all patients were assessed with the Liebowitz Social Anxiety Scale (LSAC). The mean MDA, SOD, GSH-Px and CAT levels in the patient group were significantly higher than those in the control group. There was a positive correlation between LSAC scores and MDA, SOD, GSH-Px and LSAC levels, and between the duration of illness, and MDA, SOD and CAT levels in the patient group. In conclusion, our results suggest that there may be a relationship between increased antioxidant enzyme levels and MDA, and SP. (c) 2008 Published by Elsevier Ireland Ltd.
Keywords: social phobia; antioxidant enzyme; MDA